Osteoid cell-derived chemokines drive bone-metastatic prostate cancer - Johnson, Catherine S.; Cook, Leah M. (Frontiers in Oncology, 2023)
One of the greatest challenges in improving prostate cancer survival is in designing new therapies to effectively target bone metastases. Up to 90% of patients with advanced prostate cancer will develop bone metastases, and the average survival for patients with metastatic prostate cancer is currently only 2-3 years. Many factors contribute to creating a favorable microenvironment for prostate tumors in bone, including cell signaling proteins produced by osteoid cells such as mesenchymal stem cells, osteoblasts, and osteocytes. This review highlights the impact of signaling proteins in the chemokine family that play important roles in promoting bone-metastatic prostate cancer progression in the bone environment and metastasis to bone. Currently identified osteoid cell-derived chemokines that drive bone-metastatic prostate cancer progression include CXCL8, CXCL12, CXCL13, CXCL16, CCL2, CCL5, and CX3CL1. These chemokines represent promising new therapeutic targets and biomarkers. These signaling pathways are complex, with many being produced by and exerting effects on a plethora of different cell types, including many different cells of the tumor-bone microenvironment as well as the tumor cells themselves. Therefore, further research will be essential to elucidating the nuances of chemokine signaling in the bone metastasis microenvironment, such as potential differences arising from distinct chemokine isoforms or cellular sources of these chemokines, as well as possible compensatory signaling through highly homologous chemokines. A greater understanding of the roles these chemokines play in the prostate tumor bone microenvironment will aid in the development of new therapies and combination treatment approaches to improve patient survival and quality of life.